Synthesis of α-oxygenated β, γ-unsaturated ketones by a catalytic rearrangement strategy. Issue 30 (18th July 2018) - Lempenauer, Luisa; Soupart, Aline; Duñach, Elisabet; Lemière, Gilles
Abstract : A straightforward two-step entry to α-oxgenated β, γ-unsaturated ketones from readily available α, β-unsaturated ketones is disclosed. Abstract : A straightforward two-step entry to α-oxgenated β, γ-unsaturated ketones from readily available α, β-unsaturated ketones is disclosed. It was found that bis(allylic) alcohols undergo a skeletal rearrangement in the presence of 1 mol% of cheap and non-corrosive p -toluenesulfonic acid. Computational studies were conducted to support the mechanism and to rationalise the influence of the catalyst acidity on the product selectivity.